Measuring what matters: A design-based development of English literacy assessment integrating climate literacy for EFL learners - Purwandani, Endah; Silvhiany, Sary; Inderawati, Rita (UPT Bahasa Universitas Tanjungpura, 2025)
Integrating climate literacy into education is increasingly crucial to prepare learners as responsible global citizens capable of addressing complex environmental challenges and promoting sustainable development. In the context of English Language Teaching (ELT), embedding climate-related content can serve a dual purpose. It enhances linguistic competence while cultivating ecological awareness, critical thinking, and social responsibility. However, there remains a lack of assessment instruments specifically designed to evaluate both English literacy and climate literacy simultaneously in EFL contexts. Therefore, this study aimed to develop a valid and reliable PISA-based English literacy assessment that integrates climate literacy for EFL learners. Employing a Design-Based Research (DBR) framework with Tessmer’s formative evaluation model, the study followed five iterative stages: self-evaluation, expert review, one-to-one evaluation, small-group testing, and field testing. The participants consisted of 422 eighth-grade students and six experts in English education and environmental literacy. Data analysis combined quantitative and qualitative approaches. Quantitative data were examined using Aiken’s V, item discrimination and difficulty indices, and Cronbach’s Alpha to determine validity and reliability. While qualitative insights were drawn from interviews and classroom observations. The findings revealed that 40 items were valid, with high reliability (α = 0.838) and balanced item difficulty. The instrument demonstrated strong content validity (Aiken’s V = 0.90–1.00) and effectively measured English literacy alongside ecoliteracy domains, encompassing knowledge (head), attitude (heart), and action (hand). The results underscore the potential of this dual-purpose assessment model to align language education with Indonesia’s curriculum transformation and the broader goals of global sustainability education worldwide. How to cite this paper: Purwandani, E., Shilviany, S., & Inderawati, R. (2025).Measuring What Matters: A Design-Based Development of English Literacy for EFL Learners. Journal of English Language Teaching Innovations and Materials (Jeltim), 7(2), 163-181. http://dx.doi.org/10.26418/jeltim.v7i2.96878